Therapeutic potential of curcumin in regenerative dentistry - Birjandi, Anahid A.; Sharpe, Paul (Frontiers in Dental Medicine, 2025)
IntroductionNatural compounds have emerged as promising candidates in drug development due to their potent immunomodulatory anti-inflammatory, antibacterial, analgesic, and healing properties. They have shown significant therapeutic potential in clinical applications, such as mouth rinses, toothpastes, and localized delivery systems. The use of natural alternatives can contribute to tackling antimicrobial resistance. Among natural compounds, curcumin has gained particular attention, demonstrating robust anti-cancer, antibiotic, and anti-inflammatory activities in numerous in vivo studies, while exhibiting a favorable safety profile for the treatment of various diseases. In this study, the remedial effects of curcumin and its metabolite, tetrahydrocurcumin, on dental pulp were explored. In addition, these results were compared with our previous findings on the effects of these natural compounds on periodontal ligament and gingival epithelial cells, further broadening our understanding of their therapeutic potential in oral disease such as caries and periodontitis.MethodsRNA sequencing was used to investigate the differentially expressed genes in dental pulp cells following treatments with curcumin and tetrahydrocurcumin.ResultsWe show that treatment of dental pulp cells with 1 μM of curcumin or tetrahydrocurcumin is sufficient to promote Wnt signaling pathway in dental pulp cells. Curcumin treatment promotes the upregulation of cellular metabolism and enhances cellular response to stress. Our enrichment analysis shows that treatment with tetrahydrocurcumin modulates the extracellular matrix and angiogenesis.ConclusionsThe findings of this study highlight the cytoprotective and regenerative properties of curcumin and tetrahydrocurcumin. These properties could be leveraged as a therapeutic approach to promote tissue regeneration in oral diseases.